Learn Azure Cosmos DB basics this weekend (In four hours). (Packt Publishing, 2022)
A hands-on course to help you master the core Azure Cosmos DB concepts. About This Video Learn Cosmos DB - partitioning, multi-model, consistency, and other important concepts Learn how to add or modify data from UI Understand security, compliance, privacy, and trust in Microsoft 365 In Detail Microsoft's Azure Cosmos DB is becoming an essential tool for creating powerful global web and mobile applications. Today's applications are required to be highly responsive and always online. To achieve low latency and high availability, instances of these applications need to be deployed in data centers that are close to their users. Applications need to respond in real time to momentous changes in usage at peak hours, store ever-increasing volumes of data, and make this data available to users in milliseconds. This course covers Cosmos DB architecture and how horizontal partitioning helps scale Cosmos DB unlimitedly. You will learn the advantages of Cosmos DB Automatic Indexing and Time to Live concepts. You will also understand Cosmos DB Global distribution, Multi-master, and Failover concepts along with Cosmos DB consistency level. Furthermore, you will learn the key features of Cosmos DB such as automatic indexing, how to insert and query data in your cosmos DB and learn to monitor Cosmos DB through account portal. By the end of this course, you will be able to create an account, change configurations according to best practices, and add/modify data using UI. Audience This course is for Microsoft Azure data engineers, database, and BI (Business Intelligence) developers, and for anyone interested in Azure's Cosmos DB service. No prior knowledge of Cosmos DB is needed.